Determinants of Economic Growth in SAARC Countries: The Roles of Financial Development and Foreign Direct Investment - Pandey, Abhishek (Economic Review of Nepal, 2024)
This study examines the impact of financial development and foreign direct investment (FDI) on economic growth in SAARC countries using data from the World Bank and IMF spanning from 1988 to 2021. Pooled OLS, random effect models, and fixed effects models are used to examine the effect of financial development and FDI on economic growth. The findings reveal a statistically significant positive relationship between FDI and GDP growth, indicating the importance of these factors in economic policymaking. There is a statistically insignificant negligible negative effect of financial development in the SAARC region. There is a need for infrastructure to support financial institutions to realize the potential benefits of financial development. The results highlight strong institutional frameworks necessary to support financial development and FDI to accelerate economic growth.